IMPLEMENTASI PEMBELAJARAN PJOK PADA MASA PANDEMI COVID-19 SEKOLAH DASAR NEGERI DI KECAMATAN NGEMPLAK KABUPATEN SLEMAN - Saputra, Muhammad Wigi; Yuliarto, Hari; Sabillah, Muhamad Ichsan (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2021)
This research aims to describe the implementation of Physical Education learning during the COVID-19 pandemic at the elementary schools in Ngemplak District, Sleman Regency, Special Region of Yogyakarta. This research was a descriptive quantitative study. The research method utilized a survey method with Google Form. The research population was all Physical Education teachers in the elementary schools located in Ngemplak District, Sleman Regency. The sampling technique utilized the total sampling by taking 22 Physical Education teachers in Ngemplak District. The data analysis technique utilized the descriptive quantitative analysis with percentages. Based on the results of the research, it can be concluded that the implementation of Physical Education learning during the Covid-19 pandemic in the elementary schools located in Ngemplak District, Sleman Regency, Special Region of Yogyakarta is as follows: in the Very Good category (36.36%), in the Good category (63.64 %), in the Moderate category (0%), in the Poor category (0%), and in the Very Poor category (0%). The majority of Physical Education teachers in elementary schools in Ngemplak District is in the Good category.